Characterizing the Value of Personalizing Search - Teevan, Jaime; Dumais, Susan; Horvitz, Eric (Proceedings of the 30th Annual ACM Conference on Research and Development in Information Retrieval (SIGIR 2007), Amsterdam, The Netherlands, 2007)
We investigate the diverse goals that people have when they issue the same query to a search engine, and the ability of current search engines to address such diversity. We quantify the potential value of personalizing search results based on this analysis. Great variance was found in the results that different individuals rated as relevant for the same query – even when the same information goal was expressed. Our analysis suggests that while search engines do a good job of ranking results to maximize global happiness, they do not do a very good job for specific individuals.